Social-Emotional Competencies in High School Students: A Bibliometric Analysis - Arango, Nilda Liset Donayre-; Arango, Nadia Enith Donayre-; Arango, Nubia Ivette Donayre-; Peña, Pedro Alexis Ramirez-; Huarcaya, Raquel Elizabeth Chacaltana-; Córdova, Gabriela Olivia Ramos- (International Journal of Membrane Science and Technology, 2023)
The development of socioemotional skills can serve as protection against the negative effects of stress and difficult situations in the classroom or at work. The aim of the study was to conduct a bibliometric study of the literature indexed in Scopus on socioemotional competencies in high school students from 2003 to 2023 worldwide. Methodologically, it was a quantitative bibliometric study. The scientific production indicators were generated from 191 documents selected from Scopus, using keywords in English ("social-emotional", "high school" and "students"). From 2013 to 2021, published papers increased (67.5%), indicating a growing interest in the subject of study. The United States is the country with the highest scientific production (65.4%), and Arizona State University with the most publications (n=8). The journal Psychology in The Schools had the highest publication (n=5), however, School Psychology Quarterly received more citations (n=302), with the author Elias, M.J. (n=6 papers) being the most cited (n=242). It is concluded that the implementation of cross-cutting programs involving socioemotional competence is increasing due to the promotion of interdisciplinarity of individuals affiliated with the globalized society. Therefore, when students have strong socio-emotional competencies, learning improves, and disruptive behaviors are reduced.